Intranasal insulin-like growth factor I (IGF-I) as a plausible future treatment of depression - Paslakis, Georgios; Blum, Werner F.; Deuschle, Michael (Medical hypotheses, 2012)
Depression remains a highly prevalent and mostly recurrent disorder causing an increased need to optimize and broaden the current therapy options. An enormous body of evidence links the regulation of specific neurotrophic proteins, like the brain-derived neurotrophic factor (BDNF), to depression and it may be assumed that the behavioral effects of antidepressants require functional BDNF signaling in the brain. Another neurotrophin, insulin-like growth factor-I (IGF-I), also produces antidepressant-like behavioral effects. Data have shown that BDNF plus IGF-I are more effective than either neurotrophin alone in activating neurotrophic cascades and promoting survival of hippocampal neurons. In fact, it has been suggested that the increase in hippocampal BDNF following antidepressant treatment or physical exercise in animal models is IGF-I-dependent and that antidepressant treatment increases IGF-I in human cerebrospinal fluid (CSF). Thus, BDNF and IGF-I seem to act synergistically in the same cascade of transmission and neuroplasticity. In order to avoid the pitfalls of systemic application (e.g. possible peripheral side effects) while directly targeting central nervous circuitries, the clinical intranasal administration of IGF-I appears to be a plausible and promising treatment option of depression.